Emotional Abuse Among High School Students - Amrutha; S. Surma; Manjunatha. P (CV. Doki Course and Training, 2026)
Emotional abuse during adolescence is a subtle yet serious form of maltreatment that can significantly affect psychological, emotional, and social development. Emotional abuse often normalised within family and school contexts, manifests through neglect, rejection, humiliation, criticism, and social isolation, making it difficult to identify during a critical developmental stage. The objective of the present study is to assess extent of emotional abuse among high school boys and girls’ students. The study consisted of a sample of 201 high school students (103 boys and 98 girls) were selected from two distinct schools in Bangalore. Data was collected utilizing the Emotional Abuse Scale, developed by Pushplatha Rajpoot. The results, indicate that girls reported higher levels of emotional abuse (M = 63.82, SD = 12.30) compared to boys (M = 60.67, SD = 7.81). This difference was statistically significant, t(199) = 2.17, p = .03, suggesting that gender plays a meaningful role in the experience of emotional abuse among high school students. The results emphasize the necessity of early detection and school-based interventions to support the mental health of adolescents. Identifying Emotional Abuse in High School Students can help educators, administrators, and policymakers create effective strategies to enhance emotional well-being to protect the psychological health of the High School Students.